2021
DOI: 10.1021/acs.nanolett.1c01843
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Spin Defects in Hexagonal Boron Nitride to Monolithic Bullseye Cavities

Abstract: Color centers in hexagonal boron nitride (hBN) are becoming an increasingly important building block for quantum photonic applications. Herein, we demonstrate the efficient coupling of recently discovered spin defects in hBN to purposely designed bullseye cavities. We show that the allmonolithic hBN cavity system exhibits an order of magnitude enhancement in the emission of the coupled boron vacancy spin defects. In addition, by comparative finite-difference time-domain modelling, we shed light on the emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…Additionally, a study of the hyperfine splitting near the ELAC could shed light on the coupling to nuclear spins [30], which could have applications in long-lived spin-based memories [42] or quantum simulation [43]. Rapid progress is being made in integrating hBN defects into nano-photonic devices with waveguides [13] and optical cavities [14,44] to achieve high signal-to-noise ratios for sensing applications. We also envision using V − B defects as quantum sensors [16] for magnetization of layered out-of-plane magnets like CrI 3 and CrBr 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study of the hyperfine splitting near the ELAC could shed light on the coupling to nuclear spins [30], which could have applications in long-lived spin-based memories [42] or quantum simulation [43]. Rapid progress is being made in integrating hBN defects into nano-photonic devices with waveguides [13] and optical cavities [14,44] to achieve high signal-to-noise ratios for sensing applications. We also envision using V − B defects as quantum sensors [16] for magnetization of layered out-of-plane magnets like CrI 3 and CrBr 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Optically addressable, spin-active defects and quantum dots in the solid-state have emerged as promising qubits and quantum sensors [1,2,3] because robust control techniques enable facile quantum gates and sensing protocols [4]. The recent advent of two-dimensional (2D) materials has stimulated the search for spin-active defects that can be integrated into van der Waals heterostructures, enabling a wide array of optoelectronic and nanophotonic devices that take advantage of its optical and spin properties [5,6,7,8,9,10,11,12,13,14]. A spin-active defect in a 2D material is especially promising for nanoscale sensing of interfacial phenomena with high sensitivity due to narrow spin transition linewidths and the ability to position these atomic-scale systems at sub-nanometer distances from the surface of a sample [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The V B − spin defect considered for spin qubits has a relatively weak, broadband emission peak on its own. However, Fröch et al [444] recently demonstrated that coupling a V B − spin qubit to a bullseye cavity (Fig. 8f) can enhance emission intensity and linewidth with negligible effects on the spin coherence time.…”
Section: Qes In Hbnmentioning
confidence: 99%
“…[430] Panel (f.) reprinted from ref. [444] One advantage of hBN over bulk hosts for defect QEs is the ability to transfer hBN layers to arbitrary substrates and integrate them in vdW heterostructures. The incorporation of hBN QEs in heterostructures with graphene QD spin qubits or other 2D spin qubits could enable a spin-photon interface and allow for optical readout of spins [286] .…”
Section: Qes In Hbnmentioning
confidence: 99%
“…To overcome this problem a few approaches based on coupling to dielectric of plasmonic cavities have been attempted. For instance, through coupling of V B − defects to dielectric bullseye, 32 plasmonic cavities, 33 the photoluminescence (PL) of V B − emitters has been dramatically enhanced. Future integration of spin defects in photonic cavities or waveguides is ultimately required to improve photon collection efficiencies and realize nanoscale quantum sensing and integrated quantum circuitry.…”
Section: Introductionmentioning
confidence: 99%